Analisis Keberhasilan Sistem Informasi Akademik Universitas Baturaja Menggunakan Human Organization Technology Fit Model - Ayu Jayanti; Dian Hafidh Zulfikar; Fathiyah Nopriani (Journal of Software Engineering Ampera, 2023)
Academic Information System (SIAKAD) is a system implemented by Baturaja University as a support for lecture activities. This study aims to determine what factors influence the success of SIAKAD using the Human Organization Technology Fit Model by applying 8 variables, namely system quality, information quality, service quality, system use, user satisfaction, structure, Environment and net benefit. Data collection was carried out by distributing questionnaires to students and lecturers of Baturaja University. Sampling using Probability Sampling with Proportionate Stratified Random Sampling technique. The data analysis used is PLS-SEM using SmartPLS 3.0 software. Based on the results of hypothesis testing of all variables, it was found that the factors that influence the success of SIAKAD are service quality 7.808, user satisfaction 8.389, have an influence on system use. Information quality 3.046 service quality 7.326 has an influence on user satisfaction. Information quality 2,605 service quality 3,671 has an influence on structure. System use 2.98 structure 4.223 environment 7.875 has an influence on net benefits and structure 9.627 has an influence on the environment. And factors that do not affect the success of SIAKAD, namely system quality 1.103 has no effect on system use, system quality 1.167 has no effect on user satisfaction, system quality 1.304 has no effect on structure, information quality 0.394 has no effect on system use and user satisfaction 0.787 has no effect on the net benefit.